Nachtregels : Words Without Thoughts Never To Heaven Go. - Bosma, Marja; Coelewij, Leontine; Deiters, Patricia; Delfgauw, Leo; Ex, Sjarel; Geerling, Let; Herst, Sonja; Hettig, Frank-Alexander; Hoenjet, Frank; Jansen, Bert; Jongstra, Atte; Schopping, Hans; et al. (Utrecht : Centraal Museum, 1991)
Besems, Korrie ; Blotkamp, Carel ; Corillon, Patrick ; Diamond, Jessica ; Dwyer, Nancy ; Gerdes, Ludger ; Finlay, Ian Hamilton ; Holzer, Jenny ; Horndash, Ulrich ; Kabakov, Ilya ; Körmeling, John ; Levine, Les ; Lucebert ; Mol, Pieter Laurens ; Nannucci, Maurizio ; Nauman, Bruce ; Neddam, Martine ; Nolte, Titus ; Peeters, Sef ; Prince, Richard ; Rammellzee ; Ruppersberg, Allen ; Ruygrok, Marc ; Sarkis ; Wodiczko, Krzysztof
Biog., tent. [5 p.]
Text Dutch-English
Nachtregels / Night Lines : Words Without Thoughts Never To Heaven Go, Centraal Museum, Utrecht, 27.04 - 15.10.1991
kunstcatalogus
Keywords: Nederland; Utrecht